The impact of wind generators on a Powe system's transient stability - Khomari, Moloantoa (Department of Electrical Engineering, 2014)
This thesis discusses the investigations carried out on the different types of wind generators and how these would affect the transient stability of a hypothetical power network as presented in this report. Focus was on the transient responses of the conventional synchronous generator’s rotor angle and terminal voltage when connected to different types of wind generators. The three different wind generator technologies explored were the squirrel cage induction generator (SCIG), doubly-fed induction generator (DFIG) and the converter driven synchronous generator (CDSG).